The tribological and wear properties of carbon-graphite composites - Morris, Justin Howard (Centre for Materials Engineering, 2015)
A range of carbon-graphites with differing properties has been evaluated for wear resistance. These include carbons with a high degree of graphitic order (natural and synthetic graphite), those with little or no such order (pitch bonded cokes, glassy carbons) and impregnated grades. Testing has been carried out using abrasive wear, dry sliding wear, particle erosion, slurry erosion, cavitation erosion and the corresponding wear rates have been related to the bulk properties of the different materials. In all tests; hardness, elastic modulus, porosity and the presence of fillers were found to influence the wear rates of the various grades. Maximum wear rates were consistently observed with the softer, more porous unfilled carbons.